2010
DOI: 10.1074/jbc.m109.038364
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Antibiotic Resistance Factor Spectinomycin Phosphotransferase from Legionella pneumophila

Abstract: Aminoglycoside phosphotransferases (APHs) constitute a diverse group of enzymes that are often the underlying cause of aminoglycoside resistance in the clinical setting. Several APHs have been extensively characterized, including the elucidation of the three-dimensional structure of two APH(3) isozymes and an APH(2؆) enzyme. Although many APHs are plasmid-encoded and are capable of inactivating numerous 2-deoxystreptmaine aminoglycosides with multiple regiospecificity, APH(9)-Ia, isolated from Legionella pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 61 publications
4
45
0
Order By: Relevance
“…Overall, it appears that AAC(6=)-Ie/ APH(2Љ)-Ia maintains a rigid conformation while binding substrate. This behavior is similar to what has been observed for APH(3=)-IIIa, another clinically important aminoglycoside resistance enzyme (6), but is in sharp contrast to what is seen for APH(9)-Ia, an enzyme whose role in antibiotic resistance is debatable (17). We have previously suggested that the absence of major conformational changes may signify that the aminoglycoside resistance enzyme is optimized for rapid drug detoxification and, thus, is an important feature of dedicated resistance enzymes (6).…”
Section: Rigid Structure Of Aac(6=)-ie/aph(2؆)-iasupporting
confidence: 82%
“…Overall, it appears that AAC(6=)-Ie/ APH(2Љ)-Ia maintains a rigid conformation while binding substrate. This behavior is similar to what has been observed for APH(3=)-IIIa, another clinically important aminoglycoside resistance enzyme (6), but is in sharp contrast to what is seen for APH(9)-Ia, an enzyme whose role in antibiotic resistance is debatable (17). We have previously suggested that the absence of major conformational changes may signify that the aminoglycoside resistance enzyme is optimized for rapid drug detoxification and, thus, is an important feature of dedicated resistance enzymes (6).…”
Section: Rigid Structure Of Aac(6=)-ie/aph(2؆)-iasupporting
confidence: 82%
“…Taken together, the inability to form an ordered solvent network and the lack of sufficient hydrogen-bonding interactions due to an altered conformation of the linker loop act synergistically to prohibit APH(3Ј)-IIIa from binding GTP, and neither contributing factor is controlled by individual amino acids. That other ATP-selective APHs cannot bind GTP for similar reasons is substantiated by comparisons with available structural data, such as the nucleotide-bound structure of APH(9)-Ia (11).…”
Section: Discussionmentioning
confidence: 97%
“…9,10 Aminoglycoside phosphotransferases (APHs) modify the 2-deoxystreptamine antibiotics by phosphorylation of their hydroxyl groups at Positions 4, 6, 3 0 , 2 00 , 3 00 , 7 00 (Fig. 1), or at Position 9 of spectinomycin 11 ). The enzymes are named according to the reaction they catalyze, the position on the aminoglycoside that they modify, their resistance profile (which nucleotides and aminoglycosides they will bind) indicated by a Roman numeral, and their genetic variability indicated by a lower-case letter.…”
Section: Introductionmentioning
confidence: 99%
“…The ATP-binding site is sandwiched between the N-terminal and C-terminal domains, with the aminoglycoside substrate-binding site located in a cleft in the C-terminal domain. There are three additional aminoglycoside phosphotransferase structures, APH(9) (spectinomycin phosphotransferase) 11 and two from the APH(3 0 ) family of enzymes, 19,20 and despite a very low sequence identity between these APH(9), APH(3 00 ), and APH(2 00 ) families, there is a marked degree of structural similarity. 11,18 Here, we report the X-ray structure, substrate profile, and kinetic mechanism of a second member of the APH(2 00 ) subfamily, the APH(2 00 )-IVa aminoglycoside phosphotransferase, and for the first time we report the determinants of NTP recognition by these clinically important enzymes.…”
Section: Introductionmentioning
confidence: 99%